The Influence of Sales Promotion and E-Service Quality on Purchase Decisions on Watsons Indonesia E-commerce - Vyanna Zuleika Wahyudi; Maya Ariyanti; Mita Kharisma (International Journal of Economics, Business and Innovation Research, 2024)
Watsons as a leading company in Asia is now launching an e-commerce application by providing beauty and health products. Watsons still finds obstacles in driving consumer purchasing decisions. Even though Watsons offers a wide range of products and services, complaints regarding sales promotions and electronic service quality are still issues that need to be addressed. Based on research conducted by Humairoh & Annas (2023), the results showed that sales promotion and service quality showed a positive and significant influence on purchasing decisions. Apart from that, this research also conducted research simultaneously and obtained the results that sales promotion and service quality simultaneously had a positive and significant effect on purchasing decisions. This theory is in line with the unit of analysis used in this research, namely the researcher uses the variables sales promotion, e-service quality and purchasing decisions. The purpose of this research is to measure the influence of sales promotion and e-service quality variables on purchasing decisions. This research applies quantitative methods with the sampling technique used is non-probability sampling which was distributed to 385 respondents via an online questionnaire, namely Google Form. The respondent criteria used include consumers who have made purchases on the Watsons Indonesia e-commerce application. The data analysis techniques used in this research are descriptive analysis, classical assumption testing and multiple linear regression analysis with the help of IBM SPSS Statistics version 25 software. The results of hypothesis testing show that sales promotion has a positive and significant effect on purchasing decisions on e-commerce Watsons Indonesia with the T test results showing the calculated T value (7.357) > T table (1.966) and a significance level of 0.000 < 0.05. E-Service Quality has a positive and significant effect on purchasing decisions at Watsons Indonesia e-commerce with the T test results showing the calculated T value (7.017) > T table (1.966) and a significance level of 0.000 < 0.05. And simultaneously Sales Promotion and e-service quality have a positive and significant effect on purchasing decisions in Watsons Indonesia e-commerce with the F test results showing the calculated F value is greater than the F table (82,210 > 2.62) and obtained 0.000 < 0.05 as the level its significance. Keywords: Sales Promotion, E-Service Quality, Purchasing Decisions, E-commerce.